VD_FINDINFO HC / 2014 / 370 vom 8. Mai 2014 - VD Tribunal cantonal (2014)
RADIATION DU RÔLE, TRANSACTION JUDICIAIRE, DÉCISION SUR FRAIS, ASSISTANCE JUDICIAIRE | 105 al. 1 CPC (CH), 109 al. 1 CPC (CH), 109 CPC (CH), 119 al. 4 CPC (CH), 241 al. 1 CPC (CH), 241 al. 2 CPC (CH), 241 al. 3 CPC (CH), 241 CPC (CH), 65 al. 2 TFJC (2010), 67 al. 2 TFJC (2010)